Microevolution and Adaptive Strategy of Psychrophilic Species Flavobacterium bomense sp. nov. Isolated From Glaciers - Liu, Qing; Liu, Hong-Can; Zhou, Yu-Guang; Xin, Yu-Hua (Frontiers in Microbiology, 2019)
Numerous mountain glaciers located on the Tibetan Plateau are inhabited by abundant microorganisms. The microorganisms on the glacier surface are exposed to the cold, barren and high-ultraviolet radiation environments. Although the microbial community composition on glaciers has been revealed by high-throughput sequencing, little is known about the microevolution and adaptive strategy of certain bacterial populations. In this study, we used a polyphasic approach to determine the taxonomic status of 11 psychrophilic Flavobacterium strains isolated from glaciers on the Tibetan Plateau and performed a comparative genomic analysis. The phylogenetic tree based on the concatenated single copy gene sequences showed the 11 strains clustered together, forming a distinct and novel clade in the genus Flavobacterium. The average nucleotide identity (ANI) values among these strains were higher than 96%. However, the values much lower than 90% between them and related species, indicated that they represent a novel species and the name Flavobacterium bomense sp. nov. is proposed. The core and accessory genomes of strains in this new Flavobacterium species showed diverse distinct patterns of gene content and metabolism pathway. In order to infer the driving evolutionary forces of the core genomes, homologous recombination was found to contribute twice as much to nucleotide substitutions as mutations. A series of genes encoding proteins with known or predicted roles in cold adaptation were found in their genomes, for example, cold shock protein, proteorhodopsin, osmoprotection and membrane-related proteins. A comparative analysis of the group with optimal growth temperature (OGT) ≤ 20˚C and the group with OGT > 20˚C of the 32 Flavobacterium type strains and 11 new strains revealed multiple amino acid substitutions, including the decrease of the proline and glutamine content and the increase of the methionine and isoleucine content in the group with OGT ≤ 20˚C, which may contribute to increased protein flexibility at low temperatures. Thus, this study discovered a novel Flavobacterium species in glaciers which has high intraspecific diversity and multiple adaptation mechanisms that enable them to cope and thrive in extreme habitats.